Careers in computers and data processing - McDaniel, Herman (New York : PBI, 1978)
Provides an overview of the data processing industry and describes more than fifty career possibilities from special librarian to systems analyst.
Includes index.
"A Petrocelli book."
Mode of access: Internet.
Keywords: Computer science -- Vocational guidance; Electronic data processing -- Vocational guidance